The Indian yearbook of comparative law 2016 - Singh, Mahendra Pal, 1940- (New Delhi : Oxford University Press, 2019)
The contributions, by eminent scholars, included in 'The Indian Yearbook of Comparative Law 2016' discuss the discipline of comparative law in India, and is of immense importance for legal scholarship around the globe. The issues covered include corporate law, constitutional law, human rights, environmental law, globalization, democracy, privatization and several other contemporary legal issues.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 17, 2019).
Keywords: Comparative law; Law -- India; Law; Jurisprudence & general issues